A study of knowledge, attitude, practices of menstrual hygiene and its waste disposal management among adolescent schoolgirls of Gadag District of Karnataka, India - Dharana, Anitha; Kale, Sapna; Mayappanavar, Ramesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Adolescence is a defining time in the development of a child that is characterized by rapid physical growth and neurological sculpting, the onset of puberty and sexual maturity. Pubescent girls from developing countries face several social stigma and cultural taboos while menstruation and during menstrual hygiene management. The present study was aimed to assess the knowledge of adolescent females regarding menstruation, their perception and hygiene practice regarding menstruation. Methods: A cross sectioned study for two months was conducted after ethical committee approval. Adolescent girl’s between 10-16 years were selected from schools and data was collected by interviewing the questions in a predesigned format. Data included sanitation status of the school, knowledge about menstruation, pre-menarche, menstrual practices and beliefs, and the effect of menstruation on school life. Data was represented using percentage and simple proportions, results were drawn to arrive at conclusions of study. Results: 1800 students were included, the mean age in the study was 13.2±1.2 years and 12 -14 years was maximum group.78.5% attained menarche by 13 years with 93% Hindus. 57.5% were unaware of knowledge and 88.6% acquired information from mother. Absenteeism from school was seen in 18.5% and 88% reported concentration problems. Dysmennorhoea was common (78%) and 45.61% visited physician. 78.7% of the participants use sanitary pads and 55% disposed by wrapping the pad in a newspaper and dumping in the dust bin. Conclusions: There is good amount of awareness about menstrual hygiene and menstrual waste disposal among schoolgirls in Gadag district. Problem of menstrual waste disposal can be addressed effectively by providing and improving sanitary facilities of toilets, water and power supply through combined effort of government interventions, school managements and proper health education of girls and parents.